Przemiany pozycji kobiety w PRL-u – wybrane konteksty - Mrozek , Justyna (Studia Edukacyjne, 2019)
The position of women in the Polish People’s Republic changed with respect to earlier historical periods. In this article the author analyzes four aspects of women’s lives: education, professional work, family and public sphere. The position of women is compared to the situation of men in each aspect. The analysis shows that there was no legal equality of men and women.